Analisis Tarif dan Penggunaan Energi Listrik pada Elektronik Sebagai Dasar Pengambilan Keputusan Penghematan Energi - Hartono; Muhammad Athaya Akbar Fauzi; Noermanhadi Rasyid Wiguna; Muhamad Krisna Adjani (CV. Hawari, 2026)
This study analyzes the electrical energy consumption of household appliances to provide a framework for energy-saving decisions. The observation was conducted using a direct measurement approach at a residential property in Cilegon, Banten, operating under the R-1/900 VA subsidized tariff category. Energy usage from a water pump, television, refrigerator, and air conditioner was monitored using a Melcoinda MTS-125 digital single-phase prepaid meter. Data compiled over three distinct one-hour observation sessions indicates that the air conditioner consumes the highest amount of energy, averaging 0.463 kWh per hour, whereas the television stands as the most efficient device at 0.063 kWh per hour. Financial estimation based on the official Rp605/kWh tariff demonstrates that air conditioning accounts for approximately 63.3% of the total recorded monthly expenditure among the observed appliances. These findings underline the strategic necessity of regulating operational intervals of heavy-load appliances to optimize household energy expenditures.